2021
DOI: 10.1163/15685381-bja10065
|View full text |Cite
|
Sign up to set email alerts
|

Sexual size dimorphism and life history traits in an island-mainland system: an overview of the lizard genus Microlophus

Abstract: Opposing life history strategies are a common result of the different ecological settings experienced by insular and continental species. Here we present a comprehensive compilation of data on sexual size dimorphism (SSD) and life history traits of Microlophus, a genus of lizards distributed in western South America and the Galápagos Islands, and test for differences between insular and continental species under life history theory expectations. Contrary to our predictions, we found no differences in SSD betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…This strong association was explained by a "reproductive selection hypothesis" which states that females lay more clutches throughout the year in aseasonal habitats, resulting in stronger sexual selection on males as the benefits of controlling territories are higher when reproduction is continuous (Machado et al, 2016). Our results showed that the body size-latitude relationships were not different between males and females, indicating that patterns of sexual size dimorphism in Microlophus are not being driven by different latitudinal gradients of male and female body size and support previous results indicating no evidence of Rensch's rule in Microlophus lizards (Toyama and Boccia, 2021). Additionally, our results suggest that the latitudinal gradients of body size in Microlophus probably do not depend on latitudinal gradients of sexual selection acting on males as expected based on the "reproductive selection hypothesis".…”
Section: Bergmann's Rule: Patternsupporting
confidence: 86%
See 3 more Smart Citations
“…This strong association was explained by a "reproductive selection hypothesis" which states that females lay more clutches throughout the year in aseasonal habitats, resulting in stronger sexual selection on males as the benefits of controlling territories are higher when reproduction is continuous (Machado et al, 2016). Our results showed that the body size-latitude relationships were not different between males and females, indicating that patterns of sexual size dimorphism in Microlophus are not being driven by different latitudinal gradients of male and female body size and support previous results indicating no evidence of Rensch's rule in Microlophus lizards (Toyama and Boccia, 2021). Additionally, our results suggest that the latitudinal gradients of body size in Microlophus probably do not depend on latitudinal gradients of sexual selection acting on males as expected based on the "reproductive selection hypothesis".…”
Section: Bergmann's Rule: Patternsupporting
confidence: 86%
“…These dynamics can result in what is termed the "island rule", the tendency of small and large taxa to exhibit trends towards gigantism and dwarfism on islands, respectively (Meiri, 2007). A previous comparison between island and mainland Microlophus species showed no differences between the average body sizes of these two groups (Toyama and Boccia, 2021), contradicting the expectations of the island rule.…”
Section: Bergmann's Rule: Patternmentioning
confidence: 92%
See 2 more Smart Citations
“…In turn, sexual dimorphism itself may also influence the outcome of the Island rule. To date, very few studies have formally tested for the validity of Rensch's rule within the context of body‐size evolution in insular settings, and those that did found diverging patterns (Anaya‐Meraz and Escobedo‐Galván 2020, Avramo et al 2021, Toyama and Boccia 2021).…”
Section: Introductionmentioning
confidence: 99%